Notes on the genus Dianous LEACH, 1819 with description of a new species from China (Coleoptera, Staphylinidae) - Wang, Wei; Tang, Liang; Luo, Yong-Ting (Zootaxa, 2019)
A new species of the Dianous calceatus complex from China is described: Dianous pengi Wang, Tang &  Luo sp. n. from Guangxi Province. New distributional records are reported for Dianous calvicollis Puthz, 2016, Dianous luteostigmaticus Rougemont, 1986 and Dianous huanghaoi Tang & Li, 2011. Diagnostic characters for all the species are illustrated.